PENGARUH PEMBIAYAAN MUSYARAKAH dan MURABAHAH TERHADAP PENDAPATAN PADA BPRS (BANK PEMBIAYAAN RAKYAT SYARIAH PATRIOT) BEKASI - M. GIVI ELGIVIA; MUFID HABIB MUSTOFA; HARUN HARUN (Institut Bisnis Muhammadiyah Bekasi, 2020)
The study aims to measure and find out how big an influence of musyarakah financing and murabahah financing to the revenue at BPRS (Bank Pembiayaan Pembiayaan Rakyat Syariah) Patriot Bekasi the year 2006-2015. This study uses multiple regression techniques which first learned of the requirement is made to know in order to be eligible. Variables t-hitung value of obtained musyarakah 1.942 with ttabel registration 2.36 so because the value –thitung - ttable is 1.942-236 so that H1 is accepted which means that partially musyarakah influence variables significantly to revenue. To the second hypothesis, namely that the values obtained murabahah variable thitung of 0.313 with ttable of 2.36 so because the value thitung ttable is 0.313 2.36 so Hois accepted which means that partially variable murabahah is not influential significant;y to revenue. From result of research using secondary data noted that there is significant influence F=8.273 more than Rtable=4.26 so that in the research of the influence F=8723 more than Rtable 4.26 so that in the research of the influence of musyarakah and murabahah positively impact revenue Bank Pembiayaan Rakyat Syariah Patriot Bekasi , with R2 of 40% and the remaining 60% is affected by other product.